Prevalence and Diversity of Hepatitis Virus Markers among Patients with Acute Febrile Jaundice in Chad - Fissou Henry Yandai; Kuan Abdoulaye Traore; Ali Mahamat Moussa; Bruno Lalidia Ouoba; Jean Bienvenue Ouoba; Mahamat Ali Bolti; Mahamat Fayiz Abakar; Mathieu Hota; Kadidja Gamougam; Bessimbaye Nadlao; Jean-Claude Uwimbabazi; Nadji Emmanuel Tao; et al. (Microbiology Research, 2021)
Only a minority of the patients with acute febrile jaundice evaluated through the Yellow Fever surveillance program were found positive for antibodies against Yellow Fever Virus (YFV). In order to characterize patients with acute febrile jaundice negative for YFV, we collected 255 sera between January to December 2019. We screened for HBV antigens, and antibodies against HCV and HEV. The seroprevalences observed were 10.6% (27/255) for HBV, 2% (5/255) for HCV, 17.3% (44/255) for HEV IgG, 4.3% (11/255) for HEV IgM, and 12.5% (32/255) for both IgG and IgM HEV. Prevalence of HEV was significantly higher in females than males (p < 0.01). HEV IgG prevalence was highest in those 20–29 years old, but the highest incidence rate (IgM positive) was in children 0–9 years old. Exposure to HEV was higher in the Sahelian zone (55.8%, 95% CI: 40.97–70.66) than in the Sudanese zone (30.2%, 95% CI: 24.01–36.37, p = 0.003). The high prevalence rates and hepatitis virus diversity underline the challenge of routine clinical diagnosis in Chad’s Yellow Fever surveillance program.